PROBLEMS FACED BY HIGH SCHOOL STUDENTS IN PLANNING CAREER FURTHER STUDY AND WORK - Subhan Iswahyudi, Muhammad; Dannur, Moh.; Malini Lubis, Fatimah; Muhammadong, Muhammadong (Jurnal Konseling Pendidikan Islam, 2023)
The goal of this study is to describe the issues that students face when trying to plan their careers, both in school and at work. This study is field research, which means that several high school kids were watched and talked to. The study's results showed that most students had trouble planning their careers because they didn't believe in their own skills and had trouble coming up with ideas or ways to solve problems. Problems: not enough self-confidence, hard to be focused, and hard to take the lead. They don't know much about jobs and have a hard time getting information about jobs after they finish school. Lack of conversation experience, which makes it seem like job talks will be hard, and lack of foreign language skills. It's hard to come up with a list of things that can help with preparing a job. It's hard to get projects done on time, and it's hard for students to do jobs that need good results.